2020
DOI: 10.1177/1077699020934195
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Numerical Framing Effects: The Interaction Effects of Gain/Loss Frames and Numerical Presentation Formats on Message Comprehension, Emotion, and Perceived Issue Seriousness

Abstract: Statistical information permeates media messages, but little is known about how the use of different presentation formats influences message processing. Thus, we explore numerical framing effects by examining how presentation formats interact with gain/loss frames to alter message processing and issue perceptions. We found that logically equivalent information embedded in gain/loss frames generated different levels of comprehension when it was presented in a frequency format. The gap, however, disappeared when… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 56 publications
0
9
0
Order By: Relevance
“…Future research should nevertheless explore similarities between the underlying processes that produce framing and anchoring effects. Accessibility, applicability, the level of elaboration, and emotions and comprehension of the number as mediators (Lee et al, 2021) could be interesting areas for comparison in future studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Future research should nevertheless explore similarities between the underlying processes that produce framing and anchoring effects. Accessibility, applicability, the level of elaboration, and emotions and comprehension of the number as mediators (Lee et al, 2021) could be interesting areas for comparison in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…Agenda setting, priming, and framing build on the assumption that mediated messages heighten the accessibility of certain concepts in individuals’ minds (Arendt & Matthes, 2014; Cacciatore et al, 2016; Price & Tewksbury, 1997). Previous research on gain- and loss-framing has shown that the way in which equivalent numerical information is presented—for example, speaking of a 6% unemployment rate or a 94% employment rate—elicits different emotional and cognitive responses (Lee et al, 2021). Similarly, presenting individuals with a high or low number might prime a sense of “bigness” or “smallness” that becomes more accessible in further judgments (Wegener et al, 2010).…”
Section: The Anchoring Effectmentioning
confidence: 99%
“…The scale asks about emotions such as “active,” “enthusiastic,” or “anxious.” A five-point Likert-type scale (strongly disagree—strongly agree) was used throughout the questionnaire. Next, we measured perceived self-efficacy with three items by Grazzini and colleagues (2018; M = 3.71, SD = .76, α = .63; e.g., “I have the feeling that I can make a difference by avoiding plastic”) and the perceived seriousness of the environmental issue with four items by B. Lee and colleagues (2021; M = 4.20, SD = .66, α = .70; e.g., “How urgent do you think it is to reduce the amount of plastic?”).…”
Section: Methodsmentioning
confidence: 99%
“…Negative emotions do not necessarily lead to the feeling of being overwhelmed and the inability to act. Indeed, when people make judgments, they are guided by heuristic cues, one of which may be their emotions (B. Lee et al, 2021).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Since statistical information can impact different perceptions of framing messages as well as message comprehension (e.g. Lee et al, 2020), we provided the same statistical evidence (e.g. A massive 8 million tons of plastic) across the messages (See Appendix).…”
Section: Study Design and Stimulus Developmentmentioning
confidence: 99%